2015
DOI: 10.3382/ps/pev247
|View full text |Cite
|
Sign up to set email alerts
|

Application of low-gossypol cottonseed meal in laying hens’ diet

Abstract: An experiment was conducted to evaluate the application of dietary low-gossypol cottonseed meal (LCSM) in layers' diets. A total of 432 40-weekold Hy-line W36 laying hens were allocated to one of the six dietary treatments with 6 replicates of 12 birds each. The control group was fed a corn-soybean meal basal diet, and the 4 experimental diets consisted of a basal diet with 50, 98.3, 144.2, or 189 g/kg LCSM, respectively (correspondingly 25%, 50%, 75%, 100% dietary protein provided by soybean meal were replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
11
20
0
Order By: Relevance
“…However, at CP contents similar to those of SBM, LCSM, and DRM may be beneficial for egg performance. Our current study was consistent with previous study, which suggested that the EW was decreased when layers were fed 189.0 g/kg LCSM with 28.11 mg/kg FG under the same Dig AA profiles [2]. One reason for the egg mass reduction was likely due to the difference in the content of SID Arg, phenylalanine (Phe), histidine (His), and leucine (Leu) between certain diets (i.e., LCSM 100 , DRM 100 , and LCSM 50 -DRM 50 ) and the SBM group (Table 3).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, at CP contents similar to those of SBM, LCSM, and DRM may be beneficial for egg performance. Our current study was consistent with previous study, which suggested that the EW was decreased when layers were fed 189.0 g/kg LCSM with 28.11 mg/kg FG under the same Dig AA profiles [2]. One reason for the egg mass reduction was likely due to the difference in the content of SID Arg, phenylalanine (Phe), histidine (His), and leucine (Leu) between certain diets (i.e., LCSM 100 , DRM 100 , and LCSM 50 -DRM 50 ) and the SBM group (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…To decrease dependence on SBM, it is essential to explore potential SBM alternatives. Cottonseed meal (CSM) and rapeseed meal (RSM) have long been considered attractive alternative protein sources for poultry diets [1,2], but anti-nutritional factors (i.e., free gossypol [FG] and glucosinolate) and the relatively low digestibility of their essential amino acids (AAs) limit their utilization [1,3]. The concentration of nutrients and anti-nutritional factors in CSM and RSM depend on the type of meal, method of oil extraction, ratio of kernel to husk, lint, and seed coat [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the negative effect of FG is related to additional level. He et al (2015) reported that 75% SBM could be replaced by low-gossypol CSM (21.76 mg/kg) without affecting the poultry growth performance. Other report also demonstrated that compared with the control group (0% CSM), 6% CSM (74.4 mg/kg FG) had no negative effects on ADFI and laying rate from 40 to 49 weeks in laying hens (Yuan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…So it is interesting to note that though FG level in FCSM-2 diets was lower than CSM diets, it had negative effect on growth performance. The reasons may be associated with the other anti-nutritional factors such as malvalic and sterculic acid (He et al, 2015), which may contribute to performance depression. Besides, it has been proved that lysine and arginine had antagonism effect.…”
Section: Discussionmentioning
confidence: 99%